"Effectiveness of self instructional pamphlet on knowledge and attitude on management and prevention of arthritis among general public in Thodukadu village, Thiruvallur district” - Prof. K. Mythili; Dr. Kavinmozhi James; Dr. Savithri K B; Mrs.Pappu.B; Ms.Kaviya.B; Ms.Kaviya.S; Ms.Poojasree.K.S; Ms.Kavibharathi.T (Revista Electronica de Veterinaria, 2024)
Aim: The purpose of this study was to assess knowledge and attitudes about the prevention and treatment of arthritis. Context: People with arthritis require enough information and comprehension in order to choose appropriate treatments, follow intricate schedules, and practice self-care. Participants and Methods: A pre-experimental design with a quantitative approach was used, and one group was evaluated both before and after the intervention. Convenience sampling was used to recruit 81 participants from the general population. An attitude scale and a structured knowledge questionnaire were used to gather data. Statistical Analysis Used: Data were analysed with descriptive and inferential statistics. Findings: In the pre-test, the general public’s mean knowledge of arthritis was 13.074, but in the post-test, it was 23.135. The test scores’ standard deviation was 2.004 for the post-test results and 4.338 for the pre-test results. These findings demonstrated the efficacy of pamphlets on arthritis education, as they were statistically significant (p < 0.05). The chi-square test confirmed a link between pre- and post-test knowledge levels, and the results showed a significant change in knowledge and attitudes after the intervention. The research findings indicate that the self-instructional pamphlet proved to be efficacious in enhancing the general public’s knowledge and attitudes on the management and prevention of arthritis.